Sustainable Luxury, Entrepreneurship, and Innovation (Environmental Footprints and Eco-design of Products and Processes,, 2018)
This book highlights different roles in entrepreneurship and innovation, based on the act of setting up a new venture in the area of sustainable luxury and fashion, which also involves cognitive and motivational characteristics. It also discusses the fact that many sustainability-promoting innovations require substantial technological advances.